Public Investment and Fiscal Policy : Lessons From the Pilot Country Studies. (Policy Papers; Policy Paper ;, 2005)
This paper reports on findings from eight pilot country studies on public investment that were carried out during the second half of 2004. The pilot country studies covered a diverse group of countries. Specifically, they included countries in Latin America (Brazil, Chile, Colombia, and Peru), Africa (Ethiopia and Ghana), the Middle East (Jordan), and Asia (India).